Synthesis and Characterization of Cyclotriphosphazenes Bearing Chalcones Derivatives - Zainab, Ngaini; Norashikin Irdawaty, Abd Rahman (Taylor & Francis Group, LLC, 2010)
A series of new cyclotriphosphazenes bearing chalcones derivatives, N3P3Cl5[OC6H4 CH CHC(O)C6H4OCnH2n+1] and N3P3[OC6H4CH CHC(O) C6H4OCnH2n+1]6, has been synthesized. A convenient synthetic method was performed from the reaction of hexachlorocyclotriphosphazenes with one and six equivalents of (E)-3-(4-(alkyloxy)phenyl)- 1-(4-hydroxyphenyl)prop-2-en-1-one (2a–c). The compounds differ in the length of alkyl groups, CnH2n+1, where n = 10, 12, and 14, respectively. All the products were obtained in high yields. The structures of the synthesized compounds were defined by elemental analysis, IR, 1H, 13C, and 31P NMR.